GAMBARAN COPING STRESS PADA SISWA SMAN 1 KOTA TEBING TINGGI DALAM MENGHADAPI KEGIATAN BELAJAR PADA PROSES TRANSISI PANDEMI - Pardosi, Yosefine Anggreini; Siahaan, Ervina Marimbun Rosmaida (LPPM Universitas HKBP Nommensen, 2025)
The decline in infection rates and the health impact of the COVID-19 virus in Indonesia has led to many regulatory changes. One of them is face-to-face learning activities that apply to the SMA Negeri 1 Tebing Tinggi. Learning activities that are again carried out face-to-face trigger stress on students who have been accustomed to doing online learning for 2 year. This study intends to find out how the description of stress coping strategies carried out by students at SMA Negeri 1 Kota Tebing Tinggi. This research is a descriptive study using a questionnaire as a data collection instrument. The statements in the questionnaire are based on the definition of coping stress that has been developed by Lazarus. In this research, it was found that the students of SMA Negeri 1 Kota Tebing Tinggi used the dominant form of coping with emotional stress focused coping and the dominant coping strategy used was self control.